La terre sigillée gallo-romaine Lieux de production du Haut Empire : implantations' produits' relations - Bémont, Colette (Documents d'archéologie française, 1986)
This book is intended to fill a senous gap which bas become wider and wider with every year that passes : the absence of an easily accessible source of information about one of the most successful and flourishing enterprises of Roman Gaul. the terra siglata industry. The volume is a collective work by over forty different archaeologists Defined by a research team pi me CNRS, the work include two complementary sets of contribution: a series of 45 notices, each on dedicated to a particular workshop (some of the workshops have been extensively dug, others have only been prospected); a series of 15 reports, some address problems of general methodology and regional history, others are concerned with the relations with the workshops in Switzerland and the Rhine Valley. The major interest of this collection of papers is that it brings to us an up to date inventory of production sites (its predecessor dates from 1968). Its originality is to have established, for the first time, a uniform series of descriptions, one per workshop, covering a wide range of headings The same information is thus available for all the workshops in a form that allows valid comparisons to be made.